Assessment of energy efficiency of customer care buildings of telecommunications companies in selected towns in Nigeria / Usman Abdulfatah Adekunle, Buhari Mohammed Manzuma and Andrew Mhya Stanley. - Adekunle, Usman Abdulfatah; Mohammed Manzuma, Buhari; Stanley, Andrew Mhya (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2020)
The importance of energy to human development cannot be overemphasized as it is a key determinant of economic development of all nations. However, the supply of energy has hardly ever been sufficient to meet up with the everincreasing demands exerted by multiplying population and industrialization. Buildings are accountable for nearly 40% of the total global annual energy consumption most of which is used for lighting and air conditioning. With the building sector having a relatively high potential for energy efficiency improvements compared to other sectors, this research therefore assessed the energy efficiency of the customer care buildings of telecommunication companies in selected towns in north-west Nigeria. This was done by finding out where and how energy is being used in the buildings by estimating the energy consumption of the buildings through assessment of the energy bills and a preliminary energy audit and benchmarking with set standard. Descriptive statistical analysis was done and it was found that 85.71% of the buildings have their HVAC systems consuming over 50% of their total energy with an average consumption of 74.58% per year. Also 57.14% of the buildings have higher energy use and energy use intensities than the benchmarks. It was concluded that the major energy consuming systems are the HVAC and lighting. It is therefore recommended that grid electricity which is the main source of energy to the buildings should be stabilized; while greater advantage should be taken of passive ventilation and cooling rather than mechanical HVAC systems.